Solubility of H2S in ammonium-based ionic liquids - Sousa, José M.M.V. (2021)
This work is inserted in a research program that consists mainly in the experimental and theoretical study of gas/liquid solubility in ionic liquids (ILs). In this study the experimental data of hydrogen sulfide solubility in ammonium-based ionic liquids, namely 2-hydroxyethylammonium acetate [2-HEA][Ace], bis(2-hydroxyethyl)ammonium acetate [B-2-HEA][Ace] and 2-hydroxyethyldiethylammonium hydrogen diacetate [2-HEDEA][H(Ace)2], were determined using a volumetric method in the 298 K to 318 K temperature range and at atmospheric pressure. The ionic liquids are functionalized with the OH group in the ammonium-based cations, in order to study the influence of hydroxyl group in the formation of hydrogen bonds between the IL-IL and IL-gas. The data gathered is modelled with the Cubic Plus Association Equation of State (CPA EoS), considering the association schemes four-sites (4C) for hydrogen sulfide and two-sites (2B) for the ILs ([2-HEA][Ace], [B-2-HEA][Ace] and [2-HEDEA][H(Ace)2]).